2018
DOI: 10.1245/s10434-018-6585-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient-Reported Outcomes After Nipple-Sparing Mastectomy and Conventional Mastectomy with Reconstruction

Abstract: Patient-reported outcomes should be discussed with women weighing the risks and benefits of NSM to provide a better understanding of expected quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 28 publications
3
58
1
2
Order By: Relevance
“…Another study showed higher body image scale scores in NSM compared to skin sparring mastectomy (SSM), but the difference was not statistically significant [22]. Other studies have also noted higher psychosocial [23] and sexual wellbeing scores in NSM patients [21].…”
Section: Novel Reconstructive Techniques: a Patient Attractormentioning
confidence: 93%
See 1 more Smart Citation
“…Another study showed higher body image scale scores in NSM compared to skin sparring mastectomy (SSM), but the difference was not statistically significant [22]. Other studies have also noted higher psychosocial [23] and sexual wellbeing scores in NSM patients [21].…”
Section: Novel Reconstructive Techniques: a Patient Attractormentioning
confidence: 93%
“…In 2018, a review of the American Society of Breast Surgeons (ASBrS) NSM database showed the majority of NSMs as being performed for prophylactic reasons [20]. Furthermore, NSM patients tend to be younger, Caucasian, and have smaller BMIs [21]. Another study showed higher body image scale scores in NSM compared to skin sparring mastectomy (SSM), but the difference was not statistically significant [22].…”
Section: Novel Reconstructive Techniques: a Patient Attractormentioning
confidence: 99%
“…A positive margin can present a major dilemma, as this leads to postmastectomy radiation therapy, which decreases patient satisfaction with their outcome 50 . In cases of an anterior tumor where I am concerned about the final margin, I often remove the overlying subcutaneous tissue and send this as a separate specimen, called final anterior tumor margin.…”
Section: Trouble Shootingmentioning
confidence: 99%
“…No que diz respeito ao tratamento cirúrgico, um estudo realizado por Romanoff et al (2018) revelou que pacientes submetidas à mastectomia poupadora de mamilo apresentaram níveis significativamente maiores de bem-estar psicossocial e bem-estar sexual que pacientes submetidas à mastectomia total. Contudo, apesar dos resultados satisfatórias, a técnica cirúrgica poupadora de mamilo possui indicações mais limitadas, sendo recomendada em pacientes com doenças em estágios precoces, biologicamente favoráveis e com tumores localizados perifericamente (ROMANOFF et al, 2018).…”
Section: Metodologiaunclassified